Increasing Learning Activeness and Outcomes in Fractions Multiplication among the Fifth Graders of Elementary School - Sabina Ndiung (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2021)
Multiplication of fractions learning in elementary schools still face some problems in term of students’ active participation and learning outcome. The purpose of this study was to describe the increase in activity and learning outcomes of the multiplication of fractions. The purpose of this study was to describe the increase in activity and learning outcomes of the multiplication of fractions. This research was a classroom action research using Kemmis & McTaggart design. This research was conducted at Watu Weri Elementary School, Lelak District, Manggarai Regency with a total of 52 research subjects. Data collection techniques were test and observation. The test used 5 items related to solving the multiplication fraction problem while the observation used observation sheets about the implementation of the action. The data were analyzed by quantitative descriptive techniques classical completeness criteria are 85%. The findings of the study indicated that the use of transparent plastic and/or the area of ​​a rectangular section can increase the activity and learning outcomes of the multiplication of fractions of fifth grade elementary school students. This study recommendeds that teachers use teaching aids to make learning fractions more meaningful and fun.